Exceptional longevity in northern peripheral populations of Wels catfish (Siluris glanis) - Kristofer Bergström; Oscar Nordahl; Peter Söderling; Per Koch-Schmidt; Tobias Borger; Petter Tibblin; Per Larsson (Scientific Reports, 2022)
Abstract Studies of life-history variation across a species range are crucial for ecological understanding and successful conservation. Here, we examined the growth and age of Wels catfish (Silurus glanis) in Sweden, which represent the northernmost populations in Europe. A total of 1183 individuals were captured, marked and released between 2006 and 2020. Mark-recapture data from 162 individuals (size range: 13–195 cm) were used to estimate von Bertalanffy growth curve parameters which revealed very slow growth rates compared to catfish within the core distribution area (central Europe). The fitted von Bertalanffy growth curve predicted a 150 cm catfish to be around 40 years old, while the largest recaptured individual (length 195 cm) was estimated to be 70 (95% CI 50–112) years old. This was substantially older than the previously documented maximum age of a catfish. The weight at length relationships in these northern peripheral populations were similar to those documented for catfish in central Europe indicating that resources did not constrain growth. This indicates that the slow growth and exceptional high age in the northern catfish populations are the result of lower temperatures and/or local adaptations.